Australia’s Law Graduate Glut - Douglas, Michael (Legal Service Bulletin Co-Operative Ltd, 2016)
Australia has too many law graduates and not enough jobs in law. Law graduates are finding employment outside of the profession, but we lack data on whether law graduates do not practise by choice, or by necessity. This article addresses this 'law graduate glut', its causes, and what should be done about it. The article identifies options for increasing the supply of positions for law graduates and reducing the supply of law graduates.